TEACHING VOCABULARY FOR YOUNG LEARNER BY USING SONGS AS THE MEDIA - Jumharia, Djamereng (Institut Agama Islam Negeri Palopo, 2013)
Teaching young learners is not an easy job. Then, vocabulary is central of language teaching and learning. Therefore, in this paper, the writer would like to elaborate some theories and practice ofÂ teaching vocabulary by using English songs as the media. Dealing with the characteristic of young learner students, as it is stated by Murphy âteacher can use songs to teach vocabulary to studentsâ.Â Song is one of appropriate ways to create a good atmosphere to make teaching and learning process fresh and interesting